Pemberian Beberapa Jenis Pupuk Kandang Untuk Mengendalikan Penyakit Puru Akar Yang Disebabkan Oleh Nematoda Meloidogyne Spp. Pada Tanaman Kedelai - Ali, Muhammad; Elfina, Yetty; ', Basuki (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aims to obtain the barnyard manure in controlling root knot nematode disease caused by Meloidogyne spp. on soybean plant. The research has been conducted at the Laboratory of Plant Pathology and at Experimental Farm Faculty of Agriculture, University of Riau, from July to October 2012. The research has been conducted experimentally arranged a completely randomized design (CRD), which consists of 4 treatments: without manure (P0), Chicken manure (P1), Goat manure (P2) and Cattle manure (P3). Each treatment was replicated 3 times. The results showed that application of chicken and cow manure were better in controlling nematodes Meloidogyne spp. as indicated in a lower gall indices. Application of chicken and goat manure increased height of soybean plants affected by nematodes Meloidogyne spp. Keywords : Soybean Plants , Meloidogyne spp. and Barnyard Manures.